2009
DOI: 10.1016/j.adolescence.2009.05.010
|View full text |Cite
|
Sign up to set email alerts
|

What parents don't know and how it may affect their children: Qualifying the disclosure–adjustment link

Abstract: Recent research has identified adolescent disclosure to parents as a powerful predictor of adolescent adjustment. We propose, however, that the common operationalization of adolescent disclosure incorporates the two separate constructs of disclosure and secrecy, and predicted that the disclosure-adjustment link can largely be explained by the unique contribution of secrecy from parents. A four-wave survey study among 309 adolescents tested these predictions. Factor analyses confirmed that disclosure and secrec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
204
7
14

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(259 citation statements)
references
References 54 publications
34
204
7
14
Order By: Relevance
“…Adolescents also engage in a wide variety of strategies to keep information from their parents, including nondisclosure, avoiding, lying, and secrecy (Keijsers and Laird 2010;Smetana 2008). Secrecy and concealment longitudinally predict more engagement in delinquent behavior (Frijns et al 2010) whereas disclosure predicts less antisocial behavior (Laird and Marrero 2010). Therefore, the type of nondisclosure strategy has important implications for later adolescent problem behavior.…”
Section: Parental Knowledge As Driven By Child Disclosurementioning
confidence: 96%
“…Adolescents also engage in a wide variety of strategies to keep information from their parents, including nondisclosure, avoiding, lying, and secrecy (Keijsers and Laird 2010;Smetana 2008). Secrecy and concealment longitudinally predict more engagement in delinquent behavior (Frijns et al 2010) whereas disclosure predicts less antisocial behavior (Laird and Marrero 2010). Therefore, the type of nondisclosure strategy has important implications for later adolescent problem behavior.…”
Section: Parental Knowledge As Driven By Child Disclosurementioning
confidence: 96%
“…Five-point response scales were used (1-never to 5-always). Several studies found a two-factor structure of the scale: disclosure and secrecy (Frijns, Keijsers, Branje, & Meeus, 2010;Tilton-Weaver et al, 2010), pointing out the importance of conceptually distinguishing between the two. Since it is not yet clear whether this structure stems from conceptual difference between disclosure and secrecy or it represents a disclosure topic specificity (disclosure items concern school and friends; secrecy items concern free time, nights and weekends), we rephrased the two secrecy items to measure disclosure (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Items are from Stattin and Kerr (2000), Kerr and Stattin (2000) but were modified to make the items appropriate for our early adolescent sample (see Laird & Marrero, 2011). We did not include the two items that tapped adolescent secrecy because Frijns et al (2010) demonstrated that the disclosure and secrecy items loaded onto different factors (see also a Canadian study Almas, Grusec, & Tackett, 2011). Mean scores were used (a age12 ¼ .83; a age13 ¼ .87).…”
Section: Measures Adolescent Information Managementmentioning
confidence: 99%